IMPLEMENTATION POLITICAL ISSUES OF IDENTITY AND POLITICAL DYNASTY IN THE 2020 SIMULTANEOUS ELECTION CAMPAIGN IN PANGKEP REGENCY - Nuryanti Mustari; Dewi Fortuna A.M.Nur; Marwah Yunida Alamin; M Ardiansyah Fahrezi Ali; Herman Herman (POLITICO, 2022)
ABSTRACTThe purpose of this research to identitfy politics is a political act with efforts to channel aspirations to influence policies, control over the distribution of values that are considered valuable to the most fundamental demands, namely self-determination on a primordial basis. In the form of violence, identity politics is reflected starting from efforts to incorporate values into regional regulations, separating government areas, the desire to land special autonomy to the emergence of a separatist movement. Meanwhile, in the context of religion, identity politics is reflected in various efforts to include religious values in the policy-making process, including the implication of sharia regulations, as well as efforts to make a city synonymous with a particular religion. The method used in this research is qualitative method. This study attempts to analyze identity politics and the issue of political dynasties in the implementation of the simultaneous regional elections in 2020. The qualitative method approach in this study was carried out in the form of a description. This study examines the literature on the phenomenon of identity politics and the issue of political dynasties in the 2020 simultaneous regional elections from various media and also other written sources to complete the review of the researcher’s discussion.Keywords: IImplementtion, identity politics, political dynasty, regional elections 2020